2004
DOI: 10.1002/humu.20039
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of ANKK1: A novel kinase gene closely linked to DRD2 on chromosome band 11q23.1

Abstract: The dopamine D2 receptor has been extensively studied in relation to alcoholism, substance abuse, and nicotine dependence. The most frequently examined polymorphism linked to this gene is the Taq1A restriction fragment length polymorphism (RFLP) (dbSNP rs1800497; g.32806C>T in GenBank AF050737.1), which has been associated with a reduction in D2 receptor density, although this is not universally accepted. The Taq1A RFLP lies 10 kB downstream of DRD2 and may therefore fall within a different coding region than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
441
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(457 citation statements)
references
References 20 publications
(18 reference statements)
2
441
0
6
Order By: Relevance
“…33 Genetic variation in DRD2 has been investigated; the TaqI A1 variant is a 32806 C4T substitution at 10 kb downstream of DRD2 and lies within a novel, as yet uncharacterized, kinase gene ANKK1. 58 Some studies, but not all, found the TaqI A1 allele resulted in a lower density of D 2 receptors in the human striatum in vitro and in vivo. [59][60][61][62] The TaqI A1 allele may be a risk factor for a variety of smoking behaviors (Table 2); [63][64][65][66][67][68] however, other studies were not able to replicate these findings.…”
Section: Mk Ho and Rf Tyndale 86mentioning
confidence: 99%
“…33 Genetic variation in DRD2 has been investigated; the TaqI A1 variant is a 32806 C4T substitution at 10 kb downstream of DRD2 and lies within a novel, as yet uncharacterized, kinase gene ANKK1. 58 Some studies, but not all, found the TaqI A1 allele resulted in a lower density of D 2 receptors in the human striatum in vitro and in vivo. [59][60][61][62] The TaqI A1 allele may be a risk factor for a variety of smoking behaviors (Table 2); [63][64][65][66][67][68] however, other studies were not able to replicate these findings.…”
Section: Mk Ho and Rf Tyndale 86mentioning
confidence: 99%
“…5 Recent findings, however, now place the TaqI-A polymorphism within an exon of an adjacent new protein kinase gene called 'ankyrin repeat and kinase domain containing 1' (ANKK1), which may influence signal transduction in the central nervous system (CNS). 6 Among those of European ancestry, the TaqI-A polymorphism is in linkage disequilibrium (LD) with the TaqI-B 5 and the DRD2 C957T, 7 although not with the À141C Ins/Del polymorphism. 8 The C957T and the À141C Ins/Del are functional alleles in the DRD2 gene that have been associated with mRNA stability and expression.…”
Section: Introductionmentioning
confidence: 99%
“…Of some interest is the fact that ANKK1 is not expressed in brain though carriers of the A1 allele appear to show associated functional activation using fMRI in the anterior cingulate gyrus [Fosella et al, 2006]. These results suggest that while TaqI A is now known to not be within the DRD2 gene and has been mapped to the ANKK1 gene [Neville et al, 2004], TaqI A may have a role in DRD2 functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel kinase gene, named ankyrin repeat kinase domain containing 1 (ANKK1) was identified that contains a single serine/threonine kinase domain and is expressed in placenta and whole spinal cord RNA [Neville et al, 2004]. The gene is a member of an extensive family of proteins involved in signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%